2005
DOI: 10.1248/cpb.53.1466
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibitory Phenylbutenoids from the Rhizomes of Zingiber cassumunar

Abstract: Phenylbutenoids 1-6 isolated previously from the CHCl 3 extracts of the rhizomes of Zingiber cassumunar, were evaluated for their cyclooxygenase-2 (COX-2) inhibitory activity along with a new isolate, 7 from the nBuOH extracts of this plant. The COX-2 inhibitory assay was performed by measuring prostaglandin E 2 production in lipopolysaccharide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
0
38
1
Order By: Relevance
“…Plai oil contains more active compounds and has various functions, for example, DMPBD 40 and phenylbutenoids inhibit COX-2 activity. 41 Furthermore, a study by Chaiyana et al also reported that sabinene and terpinene-4-ol could reduce the expression of nuclear factor-kappa and interleukin-6 released in human peripheral blood mononuclear cells, which reflected the compounds' anti-inflammatory activity. 18 Unfortunately, this study did not evaluate the effect of application of neurofen and Plai oil on anti-inflammatory pathways, which may be studied more in the future.…”
mentioning
confidence: 97%
“…Plai oil contains more active compounds and has various functions, for example, DMPBD 40 and phenylbutenoids inhibit COX-2 activity. 41 Furthermore, a study by Chaiyana et al also reported that sabinene and terpinene-4-ol could reduce the expression of nuclear factor-kappa and interleukin-6 released in human peripheral blood mononuclear cells, which reflected the compounds' anti-inflammatory activity. 18 Unfortunately, this study did not evaluate the effect of application of neurofen and Plai oil on anti-inflammatory pathways, which may be studied more in the future.…”
mentioning
confidence: 97%
“…Nevertheless, the inside mechanisms of these two compounds may not be similar. Dexamethasone has been reported to strongly suppress prostaglandin E2 production, (Newton et al, 1998) while compound D has no inhibitory effect on lipopolysaccharide-induced prostaglandin E2 synthesis (Han et al, 2005). This indicates that the antiinflammatory effect of compound D is not involved in the cyclooxygenase pathway.…”
Section: Resultsmentioning
confidence: 98%
“…1. Zingiber cassumunar has been reported with IC 50 (inhibition concentration at 50%) values against COX-2, ranging from 2.71 to 20.98 µM (Han, 2005). The first two compounds are structurally related to phenyl propane, which are 4-(3,4-dimethoxy-phenyl)but-1,3-diene (DMPBD), 4-[2,4,5-trimethoxy-phenyl)but-1,3-diene (TMPBD), and showed high IC 50 of 14.97 and 20.68 µM, respectively (Fig.…”
Section: Chemical Constituents and Anti-inflammatory Activity Of Prasmentioning
confidence: 99%